Method for manufacturing bonded body

By using Ag, Cu and Ti solder materials with endothermic peaks in the range of 550°C to 700°C, the problem of difficulty in joining the ceramic substrate and the metal plate at low temperature is solved, and efficient and low-cost bonding is achieved, reducing the Thermal stress and improve reliability.

CN119501220APending Publication Date: 2025-02-25SPECIAL CERAMIC MATERIALS CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411797765.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2020-02-17
Filing Date
2021-02-10
Publication Date
2025-02-25

AI Technical Summary

Technical Problem

The prior art is difficult to achieve efficient bonding between ceramic substrates and metal plates at low temperatures, and the amount of Ag in the solder material used is large, resulting in high cost.

Method used

A solder material containing Ag, Cu and Ti is used to measure the endothermic peak in the range of 550°C to 700°C in the temperature increase step by a differential scanning calorimeter (DSC) to achieve low temperature bonding.

Benefits of technology

Efficient bonding between ceramic substrate and metal plate is achieved below 800°C, reducing thermal stress, reducing costs, and improving the reliability of the joint.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119501220A_ABST
    Figure CN119501220A_ABST
Patent Text Reader

Abstract

The invention relates to a method for manufacturing a joined body. According to one embodiment of the present invention, a brazing filler metal for joining a ceramic substrate and a metal plate has an endothermic peak in the range of 550 DEG C to 700 DEG C in a temperature rise step when a differential scanning calorimeter (DSC) is used to measure a DSC curve. The brazing filler metal preferably contains Ag, Cu, and Ti. It is preferable that the brazing material have two or more endothermic peaks in the range of 550 DEG C to 650 DEG C in the temperature raising step.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] This application is a divisional application of Chinese application number 202180007559.5, with the filing date of February 10, 2021 and the invention name of “Brazing material, joint body, ceramic circuit substrate and method for manufacturing joint body”. Technical Field

[0002] The embodiments described below relate to a brazing material, a bonded body, a ceramic circuit substrate, and a method for producing a bonded body. Background Art

[0003] The joint body of a ceramic substrate and a copper plate is used as a circuit substrate equipped with semiconductor elements and the like. In International Publication No. 2018 / 021472 (Patent Document 1), a ceramic copper circuit substrate formed by joining a ceramic substrate and a copper plate is disclosed. In Patent Document 1, a solder containing Ag, Cu, Ti, etc. is used in the joining layer. In addition, the TCT characteristics are improved by controlling the nanoindentation hardness of the joining layer. In Patent Document 1, the nanoindentation hardness is controlled by allowing AgTi crystals or TiC to exist in the joining layer. In Patent Document 1, the joining strength and TCT characteristics are improved by controlling the nanoindentation hardness.

[0004] In Patent Document 1, bonding is performed at a high temperature of 780 to 850°C. If the bonding temperature is high, the burden on the bonding equipment increases. In addition, during high-temperature bonding, thermal stress is applied to the ceramic substrate or the copper plate. The load of thermal stress may cause deformation of the ceramic copper circuit substrate. Therefore, bonding at a lower temperature is required.

[0005] For example, International Publication No. 2018 / 199060 (Patent Document 2) discloses a ceramic copper circuit substrate bonded at a bonding temperature of 720 to 800°C.

[0006] Prior art literature

[0007] Patent Literature

[0008] Patent Document 1: International Publication No. 2018 / 021472

[0009] Patent Document 2: International Publication No. 2018 / 199060

[0010] Patent Document 3: Japanese Patent No. 5720839 Summary of the invention

[0011] Problems to be solved by the invention

[0012] Patent document 2 has a lower bonding temperature than patent document 1, thus achieving thermal stress relaxation. On the other hand, patent document 2 aims to diffuse Ag into the copper plate, so the amount of Ag in the bonding brazing material is large. Therefore, the cost burden is large. For example, a CuSnTi brazing material is disclosed in Japanese Patent Gazette No. 5720839 (patent document 3). By using a brazing material that does not contain Ag, bonding at 650°C is achieved. However, in patent document 3, since the Ti material is sputtered, it is not suitable for large substrates.

[0013] The present invention is an invention for coping with such a problem, and is an invention for providing a brazing material capable of bonding at a low temperature.

[0014] Means for solving problems

[0015] The brazing material according to the embodiment is a brazing material for bonding a ceramic substrate to a metal plate. The brazing material is characterized in that, when a DSC curve is measured by a differential scanning calorimeter (DSC), the brazing material has an endothermic peak in the range of 550°C to 700°C in a heating process. BRIEF DESCRIPTION OF THE DRAWINGS

[0016] Figure 1 is a schematic diagram illustrating a DSC curve.

[0017] Figure 2 This is a diagram for explaining the method of calculating the peak height in a DSC curve.

[0018] Figure 3 It is the temperature program used to determine the DSC chart.

[0019] Figure 4 This is an example of the DSC curve of the temperature increase step of Example 1 (450° C. or more).

[0020] Figure 5 This is an example of the DSC curve of the temperature drop step of Example 1 (450° C. or more).

[0021] Figure 6 This is an example of the DSC curve of the temperature increase step of Comparative Example 1 (450° C. or higher).

[0022] Figure 7 This is an example of the DSC curve of the temperature drop step of Comparative Example 1 (450° C. or more).

[0023] Figure 8 This is an example of the DSC curve of the temperature increase step of Example 2 (450° C. or more).

[0024] Fig. 9 This is an example of the DSC curve of the temperature drop step of Example 2 (450° C. or more).

[0025] Fig.10 This is an example of the DSC curve of the temperature increase step of Example 3 (550° C. or less).

[0026] Fig.11 This is an example of the DSC curve of the temperature drop step of Example 3 (550° C. or less).

[0027] Fig.12 This is an example of the DSC curve of the temperature increase step of Example 4 (550° C. or less).

[0028] Fig.13 This is an example of the DSC curve of the temperature drop step of Example 4 (550° C. or less).

[0029] Fig.14 This is an example of the DSC curve of the temperature increase step of Example 5 (550° C. or less).

[0030] Fig.15 This is an example of the DSC curve of the temperature drop step of Example 5 (550° C. or less).

[0031] Fig.16 It is a diagram showing an example of a joint body using the brazing material according to the embodiment.

[0032] Fig.17 It is a diagram showing an example of a ceramic circuit board using the brazing material according to the embodiment.

[0033] Fig.18 It is a diagram showing an example of a ceramic circuit board using the brazing material according to the embodiment.

[0034] Fig.19 It is a diagram showing an example of a ceramic circuit board using the brazing material according to the embodiment. DETAILED DESCRIPTION

[0035] In one embodiment, a brazing material for bonding a ceramic substrate to a copper plate contains Ag, Cu, and Ti, and is characterized in that when a DSC curve of the brazing material is measured by a differential scanning calorimeter (DSC), it has an endothermic peak in the range of 550°C to 700°C in a heating step.

[0036] The brazing material involved in the embodiment is a brazing material for joining a ceramic substrate to a metal plate. As the ceramic substrate, silicon nitride substrate, aluminum nitride substrate, aluminum oxide substrate, Alusil high silicon heat-resistant aluminum alloy substrate, etc. can be listed. Alusil high silicon heat-resistant aluminum alloy substrate is a substrate obtained by mixing aluminum oxide and zirconium oxide. As the metal plate, copper plate, aluminum plate, etc. can be listed. The copper plate is not limited to a pure copper plate, but can also be a copper alloy plate. As the copper plate, the copper plate shown in JIS-H-3100 can be listed. Among them, oxygen-free copper (copper purity is 99.96wt% or more) is preferred.

[0037] The brazing filler metal is preferably an active metal brazing filler metal. The active metal is one selected from Ti (titanium), Zr (zirconium) and Hf (hafnium). The joining method using the active metal brazing filler metal is called the active metal joining method. Among the active metals, Ti is preferred. Ti is a metal that is more active than Zr and Hf. In addition, the cost of Ti is cheaper than Zr and Hf. The active metal is not limited to a single metal, and can also be added to the brazing filler metal as a compound. As the compound, hydrides, oxides, nitrides, etc. can be listed.

[0038] The joining method using active metal brazing filler metal is called active metal joining method. The active metal joining method is a method of manufacturing a joint body by arranging active metal brazing filler metal between a ceramic substrate and a metal plate and performing heating and joining. By heating and joining, the active metal brazing filler metal becomes a joining layer. That is, the active metal brazing filler metal corresponds to the brazing filler metal before joining. The joining layer represents the state after joining.

[0039] In the active metal bonding method, the active metal reacts with the ceramic to form a reaction layer. When Ti (titanium) is used as the active metal, Ti reacts with the ceramic substrate to form a Ti reaction layer. When a nitride-based ceramic substrate is used, a Ti reaction layer with titanium nitride (TiN) as the main component is formed. In addition, when an oxide-based ceramic substrate is used, a Ti reaction layer with titanium oxide (TiO2) as the main component is formed. It should be noted that the nitride-based ceramic substrate refers to a silicon nitride substrate and an aluminum nitride substrate. The oxide-based ceramic substrate refers to an aluminum oxide substrate and an Alusil high-silicon heat-resistant aluminum alloy substrate. In addition, a portion of the active metal brazing layer can also be diffused into the metal plate by heating and bonding.

[0040] The solder preferably contains one or more than two selected from Ag (silver), Cu (copper), Sn (tin), In (indium) and C (carbon) as components other than active metals. Ag or Cu is a component of the base material of the solder. In addition, Sn or In has the effect of lowering the melting point of the solder. In addition, C has the effect of controlling the fluidity of the solder or reacting with other components to control the structure of the bonding layer. Therefore, as the components of the solder, Ag-Cu-Ti, Ag-Cu-Sn-Ti, Ag-Cu-Ti-C, Ag-Cu-Sn-Ti-C, Ag-Ti, Cu-Ti, Ag-Sn-Ti, Cu-Sn-Ti, Ag-Ti-C, Cu-Ti-C, Ag-Sn-Ti-C, Cu-Sn-Ti-C can be listed. In can also be used instead of Sn. Both Sn and In can also be used. Low melting point metals such as Bi (bismuth), Sb (antimony), and Ga (gallium) can also be used instead of Sn or In.

[0041] First, the DSC curve of the brazing material is measured by a differential scanning calorimeter (DSC). The differential scanning calorimeter applies heat to the sample and measures the presence or absence of an endothermic reaction or an exothermic reaction. If an endothermic reaction or an exothermic reaction occurs, a peak is generated in the DSC curve. The peak in the negative direction indicates an endothermic reaction. The peak in the positive direction indicates an exothermic reaction. An endothermic reaction indicates that the sample has been melted, decomposed, etc. An exothermic reaction indicates that the constituent elements of the sample react with each other to form a compound (including alloying) or solidify. It is known that the larger the peak, the greater the heat of reaction. Here, the peak in the negative direction is called an endothermic peak, and the peak in the positive direction is called an exothermic peak. In addition, the top of the peak is called the peak top. The difference between the maximum point and the minimum point of the peak is called the peak height.

[0042] Figure 1 is a schematic diagram illustrating a DSC curve.

[0043] Figure 1 In the graph, the horizontal axis represents temperature (°C) and the vertical axis represents heat flux (mW / mg). Figure 1 In the example of , a positive peak is generated at 300°C. This indicates that an exothermic reaction occurs at 300°C. In addition, a negative peak is generated at 600°C. This indicates that an endothermic reaction occurs at 600°C.

[0044] Figure 2 (a) and Figure 2 (b) is a diagram for explaining a method for calculating the peak height in a DSC curve.

[0045] exist Figure 2 In (a), the peak in the positive direction is illustrated. exist Figure 2 (b) shows a peak in the negative direction. Figure 2(a) and Figure 2 As shown in (b), a baseline extension line B1 is generated on the left side of the peak (left when facing the paper). The baseline extension line B1 is a horizontal line starting from the root of the left side of the peak (the so-called peak starting point). A tangent line T1 is generated as the longest straight line on the left side of the peak. An intersection X between the baseline extension line B1 and the tangent line T1 is generated. A baseline extension line B2 is generated on the right side of the peak (right when facing the paper). The baseline extension line B2 is a horizontal line starting from the root of the right side of the peak (the so-called peak end point). A tangent line T2 is generated as the longest straight line on the right side of the peak. An intersection Y between the baseline extension line B2 and the tangent line T2 is generated. An intersection M is generated between the XY straight line connecting the intersection X and the intersection Y and the line extending vertically downward from the peak top P to the horizontal axis. The distance between the intersection M and the peak top P is defined as the peak height H. Here, when the temperature is increased or decreased, a graph with a peak height H of more than 0.01 mW / mg is extracted as a peak.

[0046] For example, since the endothermic peak is in the negative direction, it rises, falls, and rises. The endothermic peak becomes a maximum point → a minimum point → a maximum point. The minimum point (the part with the lowest drop) becomes the peak top. In addition, the larger value of the minimum point on the low temperature side and the high temperature side is set as the maximum point. The peak height becomes the value obtained by subtracting the minimum point from the maximum point.

[0047] Since the exothermic peak is in the positive direction, it falls, rises, and gradually falls. The exothermic peak becomes a minimum point → a maximum point → a minimum point. The maximum point (the part with the highest rise) becomes the peak top. In addition, the larger value of the minimum point on the low temperature side and the high temperature side of the maximum point is set as the minimum point. The peak height becomes the value obtained by subtracting the minimum point from the maximum point.

[0048] It should be noted that the end point of an endothermic peak (negative peak) is sometimes also seen in an exothermic peak (positive peak), but is counted as an exothermic peak here. In addition, it is set so that each peak can be obtained by drawing an extended baseline.

[0049] Figure 3 represents the temperature program used to determine the DSC curve. Figure 3 In the figure, the horizontal axis represents time (minutes) and the vertical axis represents temperature (°C). The temperature rise process is to raise the temperature from room temperature to 500°C at a heating rate of 5°C / min. Then, the temperature is kept at 500°C for 60 minutes. Then, the temperature rise process is to raise the temperature to 845°C at a heating rate of 5°C / min. Thereafter, the temperature of 845°C is kept for 30 minutes. The temperature drop process is to drop the temperature from 845°C to room temperature at a cooling rate of 5°C / min.

[0050] In addition, as DSC, a TGA-DSC simultaneous thermal analysis device STA449-F3-Jupiter manufactured by NETZSCH or a device having equivalent performance thereto can be used. In addition, the measurement is carried out by dropping an appropriate amount of brazing material into an alumina container and in an Ar (argon) gas flow. It is necessary to prevent the brazing material from reacting with the atmosphere by conducting the measurement in an Ar atmosphere. In addition, the flow rate of the Ar gas flow is set to: 20 ml / min on the sample side and 200 ml / min on the cooling side. It should be noted that the amount of dripping (mg) is measured using a balance. By the above method, a DSC curve in the range of 100°C to 845°C is measured. That is, the so-called DSC curve is a curve obtained by plotting the change in heat flux relative to temperature using DSC. In addition, the DSC recorded in the vertical axis of the DSC curve represents the heat flux (heat flux) measured by DSC.

[0051] In addition, it is preferable to measure the DSC curve of the brazing material before the joining step. When measuring the DSC curve from the state of the joined body, the measurement is performed using a sample obtained by cutting out the joining layer from the joined body.

[0052] The bonding layer in the joint body is present between the ceramic substrate and the metal plate. In the case of preparing a sample obtained by cutting out the bonding layer from the joint body, the ceramic substrate and the metal plate are not included. The Ti reaction layer present on the surface of the ceramic substrate can be included in the bonding layer. In the case where it is difficult to cut off at the boundary between the ceramic substrate and the Ti reaction layer, a part of the Ti reaction layer can also be included in the sample.

[0053] In addition, the active metal brazing filler metal diffuses into the metal plates and is gradually joined. When preparing a sample obtained by cutting out the joining layer from the joined body, the region diffused into the metal plates is not included. That is, only the joining layer portion is set as the measurement sample.

[0054] For example, if Ag-Cu-Ti based active metal brazing material is used to join copper plates, the brazing material gradually diffuses into the copper plates. Since Cu is used in the brazing material component, it may become difficult to distinguish the boundary between the joining layer and the copper plate. Therefore, the boundary is set within 20 μm from the Ti reaction layer toward the copper plate. In addition, the sample cut out is set to 1 g.

[0055] The brazing material according to the embodiment is characterized by having an endothermic peak in the range of 550° C. to 700° C. in the temperature raising step.

[0056] Figure 4 The DSC curve in the temperature increasing step of Example 1 is shown. Figure 4 In the graph, the horizontal axis represents temperature (° C.), and the vertical axis represents heat flux (mW / mg). The heat flux is recorded as DSC. Figure 4The range of 450° C. or higher in the DSC curve of 100° C. to 845° C. is shown. In the embodiment, patterns with a peak height of 0.01 mW / mg or more are counted as peaks.

[0057] Figure 4 In the results, endothermic peaks were detected at 498°C, 606°C, 671°C, and 713°C. In addition, exothermic peaks were detected at 581°C and 619°C. Although not shown in the figure, as shown in Table 3, endothermic peaks were also detected at 172°C and 498°C. Similarly, an exothermic peak was detected at 224°C.

[0058] Figure 4 In the temperature rise process, two endothermic peaks were detected in the range of 550°C to 700°C. The endothermic reaction indicates that the solder melted, decomposed, etc. The generation of the endothermic peak in the range of 550°C to 700°C indicates that the solder melted in this temperature range. The melting of the solder indicates that a joining reaction occurred.

[0059] The peak height of at least one of the endothermic peaks at 550 to 700° C. is preferably 0.04 mW / mg or more. The peak height indicates the magnitude of the reaction. By having a large endothermic peak, bonding within this temperature range can be performed. Therefore, the peak height is preferably 0.04 mW / mg or more, and more preferably 0.07 mW / mg or more.

[0060] The brazing material preferably contains Ag (silver), Cu (copper) and Ti (titanium). The brazing material containing Ag, Cu and Ti is a kind of active metal brazing material. The active metal brazing material can firmly join the ceramic substrate and the copper plate. Since the brazing material has an endothermic peak at 550 to 700°C in the heating process, the joining temperature can be set to 800°C or less.

[0061] In addition, the brazing material preferably has two or more endothermic peaks in the range of 550°C to 650°C in the heating process. Even if there is only one endothermic peak, bonding is possible. The so-called having two or more endothermic peaks means that a melting reaction occurs at multiple stages. By melting at multiple stages, the bonding layer changes and the reaction progresses. In addition, the peak height of at least one of the endothermic peaks at 550 to 650°C is preferably 0.04 mW / mg or more.

[0062] In addition, when comparing the endothermic peak at 550-650°C in the heating process with the endothermic peak at 700°C or above, the endothermic peak at 550-650°C is preferably larger. That is, the peak height of the endothermic peak at 550-650°C in the heating process is greater than the peak height of the endothermic peak at 700°C or above in the heating process. In the case where there are two or more endothermic peaks in the range of 550-650°C, the largest peak is used as a reference. In addition, in the case where there are two or more endothermic peaks at 700°C or above, the peak with the largest peak height is used as a reference. The peak with the largest peak height is referred to as the maximum peak.

[0063] The so-called greater endothermic peak at 550-650°C indicates that no large melting reaction occurs at 700°C or above. In addition, when comparing the ratio of peak heights, the ratio is preferably greater than 2. The ratio is expressed as (peak height of the largest endothermic peak at 550-650°C) / (peak height of the largest endothermic peak at 700°C or above). If the peak ratio is greater than 2, it can be said that the main melting reaction is completed within the range of 550-650°C. In addition, the smaller the peak height of the endothermic peak at 700°C or above, the better. It is most preferred that there is no endothermic peak at 700°C or above. The smaller the endothermic peak at 700°C or above, the less melting reaction occurs. In other words, the smaller the endothermic peak at 700°C or above, the more the melting reaction is substantially completed below 700°C, and further at 550-650°C.

[0064] The brazing material preferably has an endothermic peak in the range of 450°C to 520°C during the heating process. In addition, the peak height of the endothermic peak in the range of 450°C to 520°C is preferably above 0.07mW / mg. In the case where Ti is contained in the brazing material by adding TiH2 (titanium hydride), a decomposition reaction into Ti and H occurs in the range of 450 to 520°C. This decomposition reaction becomes the main body of the endothermic reaction. The decomposed hydrogen has the effect of removing oxygen from the brazing material or activating the metal component. It should be noted that when adding hydrides other than Ti simple substance, this endothermic peak may not be present.

[0065] The brazing material preferably has one or both of an endothermic peak and an exothermic peak in the range of 140° C. to 300° C. in the DSC curve of the heating process. The peak height of either the endothermic peak or the exothermic peak in the range of 140° C. to 300° C. is preferably 0.04 mW / mg or more. Fig.10 This is a DSC curve showing the temperature increase step of Example 3. Fig.10 The DSC curve of 100° C. to 845° C. shows a range of 550° C. or less. As shown in Table 3 described later, endothermic peaks are detected at 172° C. and 220° C. In addition, exothermic peaks are detected at 217° C. and 232° C.

[0066] In order to generate an endothermic peak or an exothermic peak in the range of 140°C to 300°C in the heating process, it is preferred that Sn (tin) is contained in the solder. For example, if Sn is contained in the Ag-Cu-Ti solder, an endothermic reaction occurs by the melting of Sn, and an exothermic reaction occurs by the formation of a SnAg compound or a SnCu compound. By generating an endothermic peak or an exothermic peak at a temperature lower than the endothermic reaction (melting reaction) of 550 to 650°C, the reaction can be promoted in multiple stages. Therefore, thermal stress can be alleviated.

[0067] It is particularly preferred to have an exothermic peak. In addition, the height of the exothermic peak is preferably 0.04 mW / mg or more. This indicates that the reaction to form the SnAg compound or the SnCu compound is fully carried out. Therefore, the height of the exothermic peak is preferably 0.04 mW / mg or more, and more preferably 0.05 mW / mg or more.

[0068] In the DSC curve of the cooling process, it is preferred that the peak in the range of 140°C to 300°C is small. The so-called small peak in the range of 140°C to 300°C in the cooling process means that the reaction to form SnAg compounds or SnCu compounds is basically not caused. That is, it means that the reaction to form SnAg compounds or SnCu compounds is fully promoted in the heating process. It should be noted that the so-called small peak means that no peak is detected or the peak height is less than 0.04mW / mg. It is most preferred that no peak is detected in the range of 140°C to 300°C in the DSC curve of the cooling process. Fig.11 The DSC curve of the temperature reduction step of Example 3 is shown in FIG. Fig.11 The DSC curve at 100° C. to 845° C. showed a peak of 550° C. or less. In addition, as shown in Table 3 described later, in the DSC curve of the temperature drop step of Example 3, no peak was detected in the range of 140° C. to 300° C.

[0069] In addition, it is preferred to have an exothermic peak at 400°C to 700°C in the cooling process. In addition, the maximum peak of the exothermic peak in the cooling process is preferably in the range of 500 to 650°C. The exothermic peak of the cooling process is generated by the formation or solidification of the compound (alloy) of the bonding layer. The thermal stress generated when the molten solder solidifies is the largest. Because after the bonding interface is formed, the interfaces with different thermal expansion coefficients are constrained to each other, so that stress caused by the thermal expansion difference is generated during cooling. When the maximum peak of the exothermic peak in the cooling process is lower than 500°C, the solidification temperature may be too low and the reliability of the bonding may be reduced. On the other hand, if it exceeds 650°C, the thermal stress may become too large.

[0070] It is important that the maximum peak of the exothermic peak in the cooling process is within the range of 500 to 650°C. By completing the solidification reaction until 500°C in the cooling process, thermal stress can be relieved. The bonding layer of the completed joint body does not have to be a completely molten structure, but can also be a partially molten structure. The partially molten bonding layer becomes a layer in which the molten structure and the unmelted structure are mixed. The unmelted structure is also called a melt-separated structure.

[0071] Furthermore, the generation temperature of the peak top of the exothermic peak of 400° C. to 700° C. in the temperature drop step is preferably 10° C. or more lower than the generation temperature of the peak top of the endothermic peak of 400° C. to 700° C. in the temperature rise step. By lowering the peak top temperature in the temperature drop step, the generation of thermal stress in the temperature drop step can be suppressed.

[0072] In addition, the brazing material preferably has an exothermic peak in the range of 450°C to 520°C in the DSC curve of the cooling process. The exothermic peak is a positive peak. The endothermic peak in the range of 450 to 520°C in the heating process is mainly caused by the decomposition reaction of TiH2. In contrast, the exothermic peak in the cooling process is caused by the exothermic reaction used for solidification of the bonding layer or formation of Ti compounds. Examples of Ti compounds include TiN (titanium nitride), AgTi, CuTi, TiC, and the like. Ti is an active metal. Compared with the presence of Ti as a single substance in the bonding layer, the bonding is more stable when it exists as a Ti compound.

[0073] Figure 5 This is a DSC curve showing the temperature drop step of Example 1. Figure 5 Indicates the range above 450°C. Figure 5 In the DSC curve of the cooling process, exothermic peaks were detected at 477°C, 602°C, 644°C, and 688°C. In the DSC curve of the cooling process, no peak was detected in the range of 140°C to 300°C. This indicates that the formation of SnAg or SnCu was promoted in the heating process. In addition, the maximum peak of the exothermic peak was detected at 500 to 650°C in the cooling process.

[0074] In addition, the brazing material composition preferably contains 0 mass % to 75 mass % of Ag (silver), 15 mass % to 85 mass % of Cu (copper), 1 mass % to 15 mass % of Ti (titanium) or TiH2 (titanium hydride). In addition, when both Ti and TiH2 are used, the total is set within the range of 1 mass % to 15 mass %. In addition, when both Ag and Cu are used, preferably Ag is 20 to 60 mass % and Cu is 15 to 40 mass %.

[0075] The solder composition may contain one or two of 1% to 50% by mass of Sn (tin) or In (indium) as required. In addition, the content of Ti or TiH2 is preferably 1% to 15% by mass, and more preferably 1% to 6% by mass. If the content of Ti is 6% by mass or less, it becomes easy to generate more than two endothermic peaks in the range of 550 to 650°C by combining with Sn or In. In addition, it is set to contain 0.1% to 2% by mass of C (carbon) as required.

[0076] Regarding the ratio of the solder composition, the total of the mixed raw materials is calculated as 100 mass%. For example, when it is composed of three kinds of Ag, Cu, and Ti, it becomes Ag+Cu+Ti=100 mass%. In addition, when it is composed of four kinds of Ag, Cu, TiH2, and In, it becomes Ag+Cu+TiH2+In=100 mass%. In addition, when it is composed of five kinds of Ag, Cu, Ti, Sn, and C, it becomes Ag+Cu+Ti+Sn+C=100 mass%.

[0077] The mass ratio Ag / Cu in the solder composition is preferably less than 1.3. The endothermic peak at 550-700°C in the heating process is a reaction that melts the solder component to generate a liquid phase. The mass ratio Ag / Cu in a general active metal solder is 2.3 (=7 / 3). This ratio is for making AgCu eutectic. If the mass ratio Ag / Cu is 2.3, no endothermic peak will be formed at 550-700°C. This is because the liquid phase generation temperature becomes higher.

[0078] The mass ratio Sn / Ag in the solder composition is preferably greater than 0.25. In addition, the mass ratio In / Ag is preferably greater than 0.25. By setting it to this range, an exothermic peak can be formed at 140 to 300°C in the heating process. The peak of 140 to 300°C in the heating process represents the endothermic reaction of Sn melting and the exothermic reaction of forming SnAg or SnCu. By increasing the amount of SnAg or SnCu formed, the liquid phase generation temperature can be set to around 600°C. Thereby, the endothermic peak of 550 to 700°C can be increased. The same is true when using low melting point metals such as In to replace Sn.

[0079] C (carbon) has the effect of lowering the solidification temperature of the bonding layer in the cooling process. Therefore, the peak top temperature of the exothermic peak of 400°C to 700°C in the cooling process can be lower than the peak top temperature of the endothermic peak of 400°C to 700°C in the heating process by 10°C or more.

[0080] The average particle size D of Ag powder as the raw material of solder 50 The average particle size D of the Cu powder is preferably 3.0 μm or less, and more preferably 2.0 μm or less. 50Preferably 6.0 μm or less, more preferably 4.0 μm or less. The average particle size D of the Ti powder or TiH2 powder 50 Preferably 6.0 μm or less, more preferably 4.0 μm or less. The average particle size D of the Sn powder or In powder 50 Preferably 6.0 μm or less, more preferably 4.0 μm or less. The average particle size D of the C powder 50 Preferably 6.0 μm or less, more preferably 4.0 μm or less.

[0081] Preferably, the average particle size D of the Ag powder 50 <The average particle size D of the Cu powder 50 Preferably, the average particle size D of the Ag powder 50 <The average particle size D of the Sn powder or In powder 50 Preferably, the average particle size D of the Cu powder 50 <The average particle size D of the Sn powder or In powder 50 By reducing the particle size of the Ag powder, the contact ratio of the Ag powder with other powders can be increased. Thus, the endothermic peak at 550 to 700 °C can be increased. Or, the endothermic peak or exothermic peak at 140 to 300 °C can be increased.

[0082] The solder as described above is suitable for a bonded body formed by bonding a ceramic substrate and a metal plate.

[0083] Examples of the ceramic substrate include a silicon nitride substrate, an aluminum nitride substrate, an alumina substrate, and an Alusil high-silicon heat-resistant aluminum alloy substrate. The thickness of the ceramic substrate is preferably 0.1 mm to 1 mm. When the substrate thickness is less than 0.1 mm, the strength may decrease. In addition, if it is thicker than 1 mm, the ceramic substrate becomes a thermal resistor, and the heat dissipation of the ceramic copper circuit substrate may decrease.

[0084] The silicon nitride substrate preferably has a three-point bending strength of 600 MPa or more. In addition, the silicon nitride substrate preferably has a thermal conductivity of 80 W / m·K or more. By increasing the strength of the silicon nitride substrate, the substrate thickness can be reduced. Therefore, the three-point bending strength of the silicon nitride substrate is preferably 600 MPa or more, more preferably 700 MPa or more. The substrate thickness of the silicon nitride substrate can be reduced to 0.40 mm or less, and further 0.30 mm or less.

[0085] The three-point bending strength of the aluminum nitride substrate is about 300 to 450 MPa. On the other hand, the thermal conductivity of the aluminum nitride substrate is 160 W / m·K or more. Since the aluminum nitride substrate has low strength, the substrate thickness is preferably 0.60 mm or more.

[0086] Although the three-point bending strength of alumina substrate is about 300 to 450 MPa, it is cheap. The three-point bending strength of Alusil high-silicon heat-resistant aluminum alloy substrate is as high as about 550 MPa, but the thermal conductivity is about 30 to 50 W / m·K.

[0087] As the ceramic substrate, a silicon nitride substrate is preferred. Since the silicon nitride substrate has high strength, excellent reliability can be obtained even when a thick copper plate is bonded.

[0088] As the metal plate, copper plates, aluminum plates, etc. can be listed. In addition, the metal plate is preferably a copper plate. The copper plate preferably has a thickness of 0.6 mm or more. The thermal conductivity of the copper plate is about 400 W / m·K. By thickening the copper plate, the heat dissipation of the circuit substrate can be improved. Therefore, the thickness of the copper plate is preferably 0.6 mm or more, and more preferably 0.8 mm or more. In addition, since the silicon nitride substrate has high strength, excellent reliability can be obtained even if a thick copper plate is joined. In other words, a silicon nitride copper circuit substrate formed by joining a silicon nitride substrate having a substrate thickness of less than 0.40 mm and a three-point bending strength of more than 600 MPa to a copper plate having a thickness of more than 0.6 mm is a preferred combination.

[0089] According to the manufacturing method of the joint body involved in the embodiment, the joining temperature can be set to 800°C or less. In addition, the joining can be performed at a maximum peak temperature of the endothermic peak present at 550 to 650°C in the heating process of the brazing material. That is, the joining temperature is above the maximum peak temperature of the endothermic peak present at 550 to 650°C in the heating process. The difference between the joining temperature and the maximum peak temperature is preferably 50°C to 100°C. As described above, the brazing material preferably has an endothermic peak at 550 to 650°C. For example, if the maximum endothermic peak is 600°C, it is preferred to set the joining temperature in the range of 650 to 700°C. It should be noted that even in this case, the joining can be performed at a temperature higher than 700°C. On the other hand, the higher the joining temperature becomes, the greater the thermal stress becomes. The so-called thermal stress is deformation that accompanies not only the reaction and solidification of the brazing material, but also the grain growth of the copper plate. By lowering the joining temperature, the thermal stress can be reduced. By reducing the thermal stress, the warping of the joint body of the ceramic substrate and the copper plate can be reduced. Furthermore, if a circuit shape is given to the metal plate of the bonded body, a ceramic circuit board is obtained. For giving the circuit shape, an etching process can be used.

[0090] If the copper plate is thickened, the thermal stress caused by the copper plate becomes larger. In addition, by increasing the size of the ceramic substrate, multiple pieces can be processed simultaneously. The so-called simultaneous processing of multiple pieces is a method of cutting a large joint body to obtain a small joint body. There is also a method of dividing the joint body or a method of dividing the ceramic circuit substrate. In order to facilitate the division, a slicing process can also be implemented.

[0091] According to the joint body of the embodiment, even if the size of the ceramic substrate is enlarged to more than 200 mm in length and more than 200 mm in width, the warping of the joint body can be reduced. Therefore, it is possible to achieve a balance between the enlargement of the size of the ceramic substrate and the thickening of the copper plate. In particular, by setting the strength of the silicon nitride substrate to more than 600 MPa, the warping of the joint body can be reduced even if the thickness of the substrate is reduced to less than 0.40 mm.

[0092] In addition, the copper plate to be joined may be pre-processed into a circuit shape, or may be a whole copper plate. The whole copper plate is etched after joining. Copper plates may also be joined on both sides of the ceramic substrate. In the case where copper plates are joined on both sides, one side may be set as a circuit and the opposite side may be set as a heat sink, or both sides may be set as circuits. In addition, in the case where copper plates are joined on both sides, the thickness of one side is preferably 0.6 mm or more.

[0093] (Example)

[0094] (Examples 1 to 6, Comparative Example 1)

[0095] As brazing material compositions, compositions shown in Tables 1 and 2 were prepared. The particle sizes of the raw material powders are shown in Table 1. TiH2 powder was used as the Ti component.

[0096] [Table 1]

[0097]

[0098] [Table 2]

[0099]

[0100] The solder components according to the examples and comparative examples were mixed with a resin binder to prepare solder pastes. A DSC curve was measured for each solder paste using a differential scanning calorimeter.

[0101] The DSC measurement device used was a TGA-DSC simultaneous thermal analysis device STA449-F3-Jupiter manufactured by NETZSCH. In addition, the measurement was performed in an Ar gas flow while dropping an appropriate amount of brazing material into an alumina container. In addition, the flow rate of the Ar gas flow during the measurement was set to 20 ml / min on the sample side and 200 ml / min on the cooling side. The temperature program was set to Figure 3 The DSC curves were measured in the range of 100°C to 845°C.

[0102] Table 3 shows the detection temperatures of the endothermic peak and the exothermic peak in the temperature rising step and the temperature falling step.

[0103] [Table 3]

[0104]

[0105] Figure 4 An example of a DSC curve (450° C. or higher) in the temperature increasing step of Example 1 is shown. Figure 5 An example of a DSC curve (450° C. or higher) in the temperature drop step of Example 1 is shown. Figure 6 An example of a DSC curve (450° C. or higher) in the temperature increasing step of Comparative Example 1 is shown. Figure 7 An example of a DSC curve (450° C. or higher) in the temperature drop step of Comparative Example 1 is shown. Figure 8 An example of a DSC curve (450° C. or higher) in the temperature raising step of Example 2 is shown. Fig. 9 An example of a DSC curve (450° C. or higher) in the temperature drop step of Example 2 is shown. Fig.10 An example of a DSC curve (550° C. or less) in the temperature increasing step of Example 3 is shown. Fig.11 An example of a DSC curve (550° C. or less) in the temperature drop step of Example 3 is shown. Fig.12 An example of a DSC curve (550° C. or less) in the temperature increasing step of Example 4 is shown. Fig.13 An example of a DSC curve (550° C. or less) in the temperature drop step of Example 4 is shown. Fig.14 An example of a DSC curve (550° C. or less) in the temperature increasing step of Example 5 is shown. Fig.15 An example of a DSC curve (550° C. or less) in the temperature drop step of Example 5 is shown.

[0106] In Comparative Example 1 ( Figure 6 ), in the temperature rising process, no endothermic peak was detected in the range of 550 to 700°C. In contrast, the solder involved in the embodiment detected an endothermic peak in the range of 550 to 700°C. When comparing the endothermic peak of 550 to 700°C with the endothermic peak in the range exceeding 700°C, the endothermic peak in the range exceeding 700°C is smaller. This indicates that the melting reaction of the solder is promoted in the range of 550 to 700°C. In addition, in Comparative Example 1 ( Figure 7 ), no exothermic peak was detected at 500-650°C.

[0107] In Examples 2, 4 and 5, two or more endothermic peaks were detected in the range of 550 to 650° C. At least one of the two endothermic peaks detected had a peak height of 0.07 mW / mg or more. In addition, in Examples 2, 4 and 5, no endothermic peak was detected at a temperature exceeding 700° C.

[0108] Next, the bonding process of the ceramic substrate and the copper plate was carried out using the brazing materials of the embodiment and the comparative example. As the ceramic substrate, a silicon nitride substrate 1 having a thermal conductivity of 90 W / m·K, a three-point bending strength of 700 MPa, and a plate thickness of 0.32 mm was prepared. In addition, a silicon nitride substrate 2 having a thermal conductivity of 85 W / m·K, a three-point bending strength of 650 MPa, and a plate thickness of 0.25 mm was prepared. An aluminum nitride substrate having a thermal conductivity of 170 W / m·K, a three-point bending strength of 400 MPa, and a plate thickness of 0.635 mm was prepared. As the copper plate, oxygen-free copper was used. A copper plate 1 having a plate thickness of 0.6 mm, a copper plate 2 having a plate thickness of 0.8 mm, and a copper plate 3 having a plate thickness of 0.3 mm were prepared.

[0109] The size of the ceramic substrate was 250 mm in length and 200 mm in width. Copper plates were bonded to both surfaces of the ceramic substrate. The warpage of the resulting bonded body was measured. In addition, the bonding strength of the copper plates was measured.

[0110] For the warpage of the assembly, measure the warpage of the long side. Observe the warpage of the ceramic substrate from the side of the assembly. Connect the ends of the long side of the ceramic substrate with a straight line. The farthest position between the straight line and the surface of the ceramic substrate is set as the warpage.

[0111] A bonded body with a warpage of 0.1 mm or less on the long side was designated as a good product (○), and a bonded body with a warpage of more than 0.1 mm was designated as a defective product (×).

[0112] In addition, the bonding strength is measured by a peel test. Specifically, a peel test sample is prepared using the bonding conditions of each embodiment and comparative example. The sample is a long copper plate bonded to a ceramic substrate. At this time, the bonding is performed in a manner such that one end of the copper plate is exposed from the ceramic substrate. The peel strength is measured by vertically stretching the exposed copper plate.

[0113] The bonded bodies with a bond strength of 20 kN / m or more were set as the best products (◎), the bonded bodies with a bond strength of 15 kN / m or more were set as good products (○), and the bonded bodies with a bond strength of 14 kN / m or less were set as defective products (×). Table 4 shows the results.

[0114] [Table 4]

[0115]

[0116] The joint body according to the embodiment has a reduced warpage even when the joint temperature is set to 800° C. or less. In addition, a high joint strength is obtained. It is found that the joint can be performed at a low temperature by controlling the endothermic peak and the exothermic peak in the DSC curve of the brazing material.

[0117] In contrast, in Comparative Example 1A, when the bonding temperature is 850°C, the bonding strength is high, but the warpage is large. This is because the thermal stress generated by bonding at high temperature is large. In addition, when the bonding temperature is lowered as in Comparative Example 1B, the bonding strength decreases.

[0118] As a reference example, a silicon nitride substrate with a size of 50 mm in length × 50 mm in width × 0.32 mm in thickness was prepared. A copper plate with a size of 50 mm in length × 50 mm in width × 0.6 mm in thickness was prepared. Using the solder of Example 1 and Comparative Example 1, the joining temperature was set to 850°C for joining. With regard to the amount of warping and the joining strength, a judgment of good quality was obtained. That is, even with the conventional solder, if the joint body is small, the warping can be reduced. On the other hand, if the joint body is set to a large size of 200 mm × 200 mm or more, the warping becomes larger. If the solder involved in the embodiment is used, the warping can be reduced while lowering the joining temperature, and the joining strength can be maintained. Therefore, the joint body of the solder involved in the embodiment has excellent mass productivity.

[0119] (Joint body)

[0120] Fig.16 It is a diagram showing an example of a joint body using the brazing material according to the embodiment. Fig.16 In the figure, 10 is a ceramic circuit substrate. 12 is a ceramic substrate. 13 is a surface metal plate. 14 is a bonding layer. 15 is a back metal plate. The surface metal plate 13 and the back metal plate 15 are each bonded to the ceramic substrate 12 via the bonding layer 14. The solder involved in the embodiment is suitable for Fig.16 By using the solder involved in the embodiment, for example, the reliability of the joint body can be improved. It should be noted that if a circuit shape is given to the surface metal plate 13 or the back metal plate 15 of the joint body, a ceramic circuit substrate 10 can be obtained. In addition, in the joint body, the vertical and horizontal dimensions of the surface metal plate 13 or the back metal plate 15 can also be the same as those of the ceramic substrate 12. The circuit shape can be given using an etching process or the like.

[0121] (Joint body·Ceramic circuit board)

[0122] Figure 17 to Figure 19 It is a diagram showing an example of a ceramic circuit board using the brazing material according to the embodiment.

[0123] exist Fig.17 In the ceramic circuit substrate 10a, two surface metal plates 13 processed into a circuit shape are bonded to the ceramic substrate 12. The embodiment is not limited to this example, and three or more surface metal plates 13 may be bonded to the ceramic substrate 12.

[0124] A through hole may be provided in the ceramic substrate. The ceramic circuit substrate preferably has a structure in which a front metal plate and a back metal plate are electrically connected via the through hole. Fig.18 An example of a ceramic circuit board having a through hole is shown. Fig.18 It is a cross-sectional view of a portion where a through hole is provided. Fig.18 In the figure, 10a is a ceramic circuit substrate, 12 is a silicon nitride substrate, 13 is a surface metal plate, 14 is a bonding layer, 18 is a back metal plate, and 19 is a through hole. Fig.18 In the embodiment, the front metal plate 13 and the back metal plate 18 are electrically connected via the through hole 19 . Fig.18 In the ceramic circuit substrate 10a, a plurality of through holes 19 respectively connect a plurality of surface metal plates 13 with a plurality of back metal plates 18. The embodiment is not limited to such a structure. In the ceramic circuit substrate 10a, the through holes 19 may be provided only for a portion of the plurality of surface metal plates 13. The through holes 19 may also be provided only for a portion of the plurality of back metal plates 18. The inside of the through holes 19 is preferably filled with the same material as the bonding layer 14. The structure inside the through holes 19 is not particularly limited as long as it can conduct electricity between the surface metal plate and the back metal plate. Therefore, a metal film may also be provided only on the inner wall of the through holes 19. On the other hand, by filling with the same material as the bonding layer 14, the bonding strength can be improved.

[0125] The silicon nitride circuit substrate according to the embodiment is suitable for a semiconductor device. In the semiconductor device, a semiconductor element is mounted on a metal plate of a ceramic circuit substrate via a bonding layer. Fig.19 An example of a semiconductor device is shown. Fig.19 In the figure, 10a is a ceramic circuit substrate, 20 is a semiconductor device, 21 is a semiconductor element, 22 is a bonding layer, 23 is a wire bonding, and 24 is a metal terminal. Fig.19 In the embodiment, a semiconductor element 21 is bonded to a metal plate of a ceramic circuit board 10a via a bonding layer 22. Similarly, a metal terminal 24 is bonded via a bonding layer 22. Adjacent metal plates are electrically connected to each other by wire bonding 23. Fig.19 In addition to the semiconductor element 21, a wire bond 23 and a metal terminal 24 are also bonded. The semiconductor device involved in the embodiment is not limited to such a structure. For example, only one of the wire bond 23 and the metal terminal 24 may be provided. The semiconductor element 21, the wire bond 23 and the metal terminal 24 may be provided in plurality on the surface metal plate 13. On the back metal plate 18, the semiconductor element 21, the wire bond 23 and the metal terminal 24 can be bonded as needed. For the metal terminal 24, various shapes such as a lead frame shape and a convex shape can be applied.

[0126] By using the brazing material according to the embodiment for the above-mentioned ceramic circuit board or semiconductor device, for example, the reliability thereof can be improved.

[0127] Several embodiments of the present invention are illustrated above, but these embodiments are presented as examples and are not intended to limit the scope of the invention. These novel embodiments can be implemented in various other ways, and various omissions, substitutions, changes, etc. can be made without departing from the scope of the main purpose of the invention. These embodiments and their variations are included in the scope and main purpose of the invention, and are also included in the invention recorded in the claims and their equivalents. In addition, the above-mentioned embodiments can be combined with each other and implemented.

Claims

1. A method for manufacturing a joint body, wherein a ceramic substrate and a copper plate are joined by heating using a brazing material, wherein: When the total amount of the raw materials contained in the brazing material is 100 mass%, the brazing material contains 20 mass% to 60 mass% of Ag, 15 mass% to 40 mass% of Cu, 1 mass% to 15 mass% of one or two of Ti or TiH2, and 1 mass% to 50 mass% of any one of Sn or In, The average particle size of Ag 50 Smaller than the average particle size D of Cu 50 , The average particle size of Ag 50 Smaller than the average particle size D of Sn or In 50 , The brazing material has an endothermic peak in the range of 550° C. to 700° C. in the temperature raising step when a DSC curve is measured by a differential scanning calorimeter (DSC).

2. The method for manufacturing a joined body according to claim 1, characterized in that: The mass ratio of Ag to Cu in the solder is 1.3 or less.

3. The method for manufacturing a joint body according to claim 1 or claim 2, characterized in that: The mass ratio of Sn to Ag or the mass ratio of In to Ag in the solder is 0.25 or more.

4. The method for manufacturing a joined body according to claim 1 or claim 2, characterized in that: The brazing material has one or both of an endothermic peak and an exothermic peak in the range of 140° C. to 300° C. in the temperature increasing step when a DSC curve is measured by a differential scanning calorimeter (DSC).

5. The method for manufacturing a joined body according to claim 3, characterized in that: The brazing material has one or both of an endothermic peak and an exothermic peak in the range of 140° C. to 300° C. in the temperature increasing step when a DSC curve is measured by a differential scanning calorimeter (DSC).

6. The method for manufacturing a joined body according to claim 1 or claim 2, characterized in that: The average particle size of Ag 50 The average particle size of Cu is less than 3.0 μm. 50 The average particle size D of Sn or In is less than 6.0 μm. 50 It is less than 6.0μm.

7. The method for manufacturing a joined body according to claim 5, characterized in that: The average particle size of Ag 50 The average particle size of Cu is less than 3.0 μm. 50 The average particle size D of Sn or In is less than 6.0 μm. 50 It is less than 6.0μm.

8. The method for manufacturing a joined body according to claim 1 or claim 2, characterized in that: The bonding temperature of the heat bonding is 800° C. or less.

9. The method for manufacturing a joined body according to claim 7, characterized in that: The bonding temperature of the heat bonding is 800° C. or less.

10. The method for manufacturing a joined body according to claim 1 or claim 2, characterized in that: The bonding temperature of the heat bonding is higher than the temperature of the maximum endothermic peak in the temperature raising step within the range of 550° C. to 650° C., The difference between the bonding temperature and the temperature of the maximum endothermic peak is 50° C. to 100° C.

11. The method for manufacturing a joined body according to claim 7, characterized in that: The bonding temperature of the heat bonding is higher than the temperature of the maximum endothermic peak in the temperature raising step within the range of 550° C. to 650° C., The difference between the bonding temperature and the temperature of the maximum endothermic peak is 50° C. to 100° C.

12. The method for manufacturing a joint body according to claim 1 or claim 2, characterized in that: The brazing material has two or more endothermic peaks in the range of 550° C. to 650° C. in the temperature raising step.

13. The method for manufacturing a joined body according to claim 11, characterized in that: The brazing material has two or more endothermic peaks in the range of 550° C. to 650° C. in the temperature raising step.

14. The method for manufacturing a joined body according to claim 1 or claim 2, characterized in that: The endothermic peak at 550° C. to 650° C. in the temperature raising step is larger than the endothermic peak at 700° C. or higher in the temperature raising step.

15. The method for manufacturing a joined body according to claim 13, characterized in that: The endothermic peak at 550° C. to 650° C. in the temperature raising step is larger than the endothermic peak at 700° C. or higher in the temperature raising step.

16. The method for manufacturing a joined body according to claim 1 or claim 2, characterized in that: There is an endothermic peak in the temperature increasing step within a range of 450°C to 520°C.

17. The method for manufacturing a joined body according to claim 15, characterized in that: There is an endothermic peak in the temperature increasing step within a range of 450°C to 520°C.

18. The method for manufacturing a joined body according to claim 1 or claim 2, characterized in that: The ceramic substrate is a silicon nitride substrate, The copper plate has a thickness of 0.3 mm or more.

19. The method for manufacturing a joined body according to claim 17, characterized in that: The ceramic substrate is a silicon nitride substrate, The copper plate has a thickness of 0.3 mm or more.

20. The method for manufacturing a joined body according to claim 1 or claim 2, characterized in that: The ceramic substrate has a size of at least 200 mm in length and at least 200 mm in width.

21. The method for manufacturing a joined body according to claim 19, characterized in that: The ceramic substrate has a size of at least 200 mm in length and at least 200 mm in width.

Citation Information

Patent Citations

  • Operating method of image data

    JP1982020839A

  • Bonding body, circuit board and semiconductor device

    WO2018021472A1

  • Ceramic circuit board, method for manufacturing ceramic circuit board, and module using ceramic circuit board

    WO2018199060A1